Climate Risk Vulnerability Assessment to inform sub-national decision making in Vietnam - Parker, Louis; Bourgoin, Clément; Martínez Valle, Armando Isaac; Läderach, Peter R.D. (International Center for Tropical Agriculture, 2018)
This project was undertaken to develop and implement a pan tropical Climate Risk Vulnerability Assessment (CRVA) that can identify through an agricultural lens and at a fine resolution which parts of the country are most vulnerable to climate change. The CRVA is adaptable to the specific national context and also flexible to data limitations. Based on the academic literature and the latest crop and climate models we aim to provide a robust and repeatable methodology. We conceptualise vulnerability as the combination of the sensitivity of the major food security crops to climate change, the exposure of the population to natural hazards and the potential for the population to respond (Adaptive Capacity). We have applied the CRVA to Vietnam and have mapped the hotspots of climate change vulnerability and identified the underlying driving indicators. The Mekong delta is a region we identified as vulnerable, as over 95% of the area is characterized by an overall decrease of climatic suitability for rice, combined with exposure to flooding, sea level rise and drought. Nonetheless, the delta is marked by relatively high adaptive capacity due to developed infrastructure, relatively high organisational capacity, education and relatively low levels of inequality (GINI).